Identifikasi Jenis-Jenis Gulma di Area Persawahan Desa Salumpaga Kec. Tolitoli Utara Kab. Tolitoli - Satri,; Nurdin, Musdalifah; Febriawan, Aan; Lilies,; Fardha, Rizka; Febriani, Vita Indri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify rice field weeds in Salumpaga Village, North Tolitoli District. Rice field weeds are wild plants that grow in rice fields and are undesirable to farmers because they inhibit the growth of rice plants. The method used was descriptive with purposive sampling techniques. The weeds identified were those that already had complete organs such as roots, stems, and leaves. The results of the study identified 25 types of weeds, namely, the Asteraceae family (Synedrella nodiflora (L.), Erigeron sumatrensis (Retz.), Ageratum conyzoides (L.), Tridax procumbens (L.), Sphogneticola trilobata (L.), Chromolaena odorata (L.) King & H.Rob, Mikania scandens (L.) and Mikania mikrantha (Kunth.)). Fabaceae family (Mimosa pudica (L.) and Crotalaria pallida (Var.)). Euphorbiaceae family (Euphorbia hirta (L.) and Macaranga peltata (Roxb.)). Cyperaceae family (Kyllinga brevifolia (Rottb.) Hassk. and Cyperus compressus (L.)). Lamiaceae family (Hyptis brevipes (Poit.) and Gmelina arborea (Roxb.)). Convolvulaceae family (Ipomoea aquatica (Forssk.) and Ipomoea triloba (L.)). Poaceae family (Hymenachne amplexicaulis (Rudge.)). Oxalidaceae family (Oxalis stricta (L.)). Rubiaceae family (Oldenlandia corymbosa (L.)). Onocleaceae family (Matteuccia sturthiopteris (L.) Tod). Family Amaranthaceae (Celosia argentea (L.)). Family Vitaceae (Cayratia trifolia (L.)). Family Graminaceae (Imperata cylindrical (L.). Beauv.).